2000
DOI: 10.2460/javma.2000.217.1021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of serum parvovirus and distemper virus antibody titers for determining revaccination strategies in healthy dogs

Abstract: The high prevalence of adequate antibody responses (CPV, 95.1%; CDV, 97.6%) in this large population of dogs suggests that annual revaccination against CPV and CDV may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 15 publications
1
58
1
3
Order By: Relevance
“…Earlier works by , Twark and Dodds (2000) and Eghafona et al, (2007) reported that sex, age and breed showed no significant association (where P > 0.05) with CDV serum antibody titer. This is also in agreement with what was reported in the literatures Waner and Keren-Kornblatt, 2006) but disagreed with Babalola et al (2015) who reported that gender affected the susceptibility of dogs to canine distemper.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Earlier works by , Twark and Dodds (2000) and Eghafona et al, (2007) reported that sex, age and breed showed no significant association (where P > 0.05) with CDV serum antibody titer. This is also in agreement with what was reported in the literatures Waner and Keren-Kornblatt, 2006) but disagreed with Babalola et al (2015) who reported that gender affected the susceptibility of dogs to canine distemper.…”
Section: Discussionmentioning
confidence: 78%
“…Reports have revealed that, vaccine failure can result from the effect of maternally derived antibody or passively acquired antibodies at time of vaccination, delay in maturation of the immune system, poor vaccinal immunogenicity, genetic inability to respond to certain vaccine antigens, immune-suppression and ineffective lots of vaccine (Schultz, 2000;. It has also been reported that some dogs never appeared to mount an adequate antibody response to vaccination (Twark and Dodds, 2000). If however, there is low antibody response to vaccination due to vaccination failure, revaccination may be required.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][8][9][10] The need for a reliable, affordable, and standardized serum antibody assay has been proposed. 9,10 In response to this idea, this study evaluated the usefulness of a commercially available standardized in-clinic dot-ELISA test kit for the semiquantitative assay of CPV and CDV IgG antibodies in dogs that had not been vaccinated for at least one year. To the authors' knowledge, this is the first study to test the applicability of an in-clinic dot-ELISA assay for the assessment of immune status in adult dogs after vaccination.…”
mentioning
confidence: 99%
“…Σήμερα υπάρχει πληθώρα επιστημονικών δεδομένων που δείχνουν ότι η διάρκεια της ανοσίας που προ σφέρουν τα ελαττωμένης λοιμογόνου δύναμης (ΕΛΔ) απαραίτητα εμβόλια υπερβαίνει κατά πολύ τα 3 χρό νια. Συγκεκριμένα, τα εμβόλια για τον παρβοϊό (του σκύλου και της γάτας), τον ιό της νόσου του Carré και τον αδενοϊό-2 προσφέρουν ανοσία με διάρκεια 7 τουλάχιστον χρόνων (Scott and Geissinger 1999, Twark and Dodds 2000, Lappin et al 2002, Gill et al 2004, Abdelmagid et al 2004, Böhm M et al 2004, Mouzin et al 2004a, Mouzin et al 2004b, Schultz 2006, Larson and Schultz 2007, Day et al 2010a, ενώ εκείνα για τον ερπητοϊό-1, τον καλυκοϊό και τον ιό της λύσσας 3 τουλάχιστον χρόνων (Scott and Geissinger 1999, Gore et al 2006, Day et al 2010a. Αντίθετα, η διάρκεια της ανοσίας που προ σφέρουν τα προαιρετικά εμβόλια κυμαίνεται γύρω στον ένα χρόνο.…”
Section: οι κυριοτερες αλλαγες στα εμβολιακα προγραμματα του σκυλου κunclassified